Chomsky's generative theory and its use in legal translation (Models between Arabic and Persian) (Journal of the College of Languages (JCL), 2023)
The research deals with the scientific and academic necessity in the field of contemporary linguistic research and translation studies called for new and advanced scientific theories in line with technological developments and modern information in the world, using different letters between the fields of science and knowledge, and thus resulted in new research methods with the linguistic phenomenon to vary its communicative functions. the overview, theories, the appearance of the formula in its wide form and the legal translation in a narrower form.        Research aims: discuss the most important content of legal language and its translation methods, equivalence and translation equivalence, translation transformations such as rearranging, addition, deletion and replacement, legal linguistic levels, including the level of legal discourse, and its relationship to other legal linguistic levels. The research adopts the qualitative field-experimental approach by benefiting from the researcher’s experiences in addition to studying a number of official translations of documents, documents, legal texts and contracts between the Arabic and Persian languages. The course of the study should be from the general to the specific, i.e. a review of the general translation, then the sworn translation, down to the problems associated with it.